The return of Martin Guerre - Lewis, Janet 1899-1998; Portal, Michel 1935- (Arrow Films. World, 2010)
The plot revolves around the unraveling of the identity of a 16th century peasant who disappeared as a young husband, and the man who returns to resume his marriage nine years later